Hubungan Kadar Serum Cancer Antigen-125 dengan Stadium Kanker Ovarium Tipe Epitel: Correlation between Serum Levels of Cancer Antigen-125 and Stages of Epithelial Type Ovarian Cancer - Lestari, Della Ayu; Rachmi, Eva; Achmad, Andika Adi Saputra (Jurnal Sains dan Kesehatan, 2024)
Ovarian cancer has the worst prognosis of all gynecologic malignancies in women. The five-year survival rate for ovarian cancer is only 30%–50% in Indonesia. The most common histological type in ovarian cancer incidence is epithelial ovarian cancer (90%). Ovarian cancer is still one of the deadliest gynecological cancers because there is no effective technique for predicting the stage of ovarian cancer. The accuracy of CA-125 as a tumor marker in determining the stage of ovarian cancer is still being argued. This study analyzes the relationship between serum CA-125 levels and the stage of epithelial type ovarian cancer at Abdoel Wahab Sjahranie Hospital Samarinda, which was conducted from August to December 2023. This research is an analytical observational with a cross-sectional approach. The sampling technique was purposive sampling, with secondary data in the form of medical records, sample totaled 30 patient. Bivariate analysis was carried out using the one way ANOVA test. The relationship between serum CA-125 levels and the stage of epithelial ovarian cancer was not significant overall (p = 0.052). Further tests revealed a significant difference between serum CA-125 levels and the stage of epithelial type ovarian cancer, especially at stage I and stage III (p = 0.027). Keywords:          Serum CA-125 Levels, Epithelial Type of Ovarian Cancer, Stage   Abstrak Kanker ovarium memiliki prognosis terburuk dari seluruh keganasan ginekologi pada wanita. Kesintasan lima tahun kanker ovarium hanya 30%–50% di Indonesia. Tipe histologis paling umum pada insidensi kanker ovarium adalah kanker ovarium tipe epitel (90%). Kanker ovarium masih menjadi salah satu kanker ginekologi paling mematikan karena belum ada teknik yang efektif untuk memprediksi stadium kanker ovarium. Akurasi CA-125 sebagai salah satu penanda tumor dalam menentukan stadium kanker ovarium masih menjadi perdebatan. Penelitian ini menganalisis hubungan antara kadar serum CA-125 dengan stadium kanker ovarium tipe epitel di RSUD Abdoel Wahab Sjahranie Samarinda, yang dilakukan pada bulan Agustus hingga Desember 2023. Penelitian ini berupa observasional analitik dengan pendekatan cross-sectional. Teknik pengambilan sampel melalui purposive sampling, dengan data sekunder berupa rekam medis. Sampel berjumlah 30 pasien. Analisis bivariat dilakukan dengan uji one way ANOVA. Hubungan antara kadar serum CA-125 dengan stadium kanker ovarium tipe epitel secara keseluruhan adalah tidak bermakna (p = 0,052). Uji lanjut didapatkan perbedaan yang bermakna antara kadar serum CA-125 dengan stadium kanker ovarium tipe epitel, khususnya pada stadium I dan stadium III (p = 0,027). Kata Kunci:         Kadar Serum CA-125, Kanker Ovarium Tipe Epitel, Stadium